Yield and nutritional requirements of cassava in response to potassium fertilizer in the second cycle - Fernandes, Adalton Mazetti [UNESP]; Gazola, Bruno [UNESP]; Nunes, Jesion Geibel da Silva [UNESP]; Garcia, Emerson Loli [UNESP]; Leonel, Magali [UNESP] (Taylor & Francis, 2017)
Potassium (K) is one of the most absorbed nutrients by cassava because it acts on the synthesis and starch accumulation in the storage roots. Here, we show that K application at the beginning of the second vegetative cycle of cassava submitted to shoot pruning increased the yield of roots and starch, and the nutrient demand of plants. Application of 45–89 kg ha−1 dipotassium oxide (K2O) in the second cycle increased the yield of storage roots and starch from 36–49% and K applied at this time had a greater effect on the synthesis and allocation of starch in the storage roots. K supply increased the accumulation of N and S by 2.0- to 3.0-fold and the accumulation of other nutrients by 1.4- to 1.7-fold. The removal of phosphorus (P), manganese (Mn), and zinc (Zn) by storage roots was not affected by K application, whereas the removal of other nutrients increased by 1.3- to 4.3-fold.
Keywords: Manihot esculenta; mineral nutrition; root weight; root yield; starch yield